Bacteriological and Physicochemical Assessment of Selected Brands of BottledWater in Ilorin, Nigeria - Sule, I.O.; Agbabiaka, T.O.; Saliu, B.K.; Bello, A.B.; Adeboye, A.B. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2017)
Twenty different brands of bottled water sold in Ilorin metropolis, Kwara State, Nigeria were examined for their bacteriological and physicochemical qualities. Bacteriological analyses were carried out to determine the counts of heterotrophic bacteria, total coliform and faecal coliform. Physicochemical qualities such as pH, chloride content, total hardness and total suspended solids were also examined. The heterotrophic bacterial count ranged from 0 to 121cfu/ml while the total coliform count ranged from 0 to 1100 coliform/100ml of the sample. There was absence of faecal coliform in the bottled water samples. The pH, chloride content, total hardness and total suspended solids ranged from 6.50 to 8.40, 3.55 to 4.79mg/l, 1 to 90mg/l, and 0.001 to 0.003 g/100ml respectively. The bacterial species isolated belong to the genera Staphylococcus, Micrococcus and Aeromonas. In terms of quality, 19 (95%), 18 (90%) and 0 (100%) of the 20 brands of bottled water samples met the standard for heterotrophic bacteria, total coliform, and faecal coliform respectively. All the bottled water samples conformed to the standard for pH, chloride content, total hardness and total suspended solids. It can be concluded from this study that 85% of the bottled waters were suitable for drinking with regard to bacteriological and physicochemical parameters tested. It is recommended that stringent measures should be adhered to in the manufacture of bottled water, the bottles should be properly capped, and information on the manufacturing date, expiry date and batch number should be written on the bottles for easy recall.